Hygrophorus deliciosus (Hygrophoraceae, Agaricales), a popular edible mushroom of the H. russula-complex from southwestern China - Wang, Chao-Qun; Li, Tai-Hui (Phytotaxa, 2020)
A popular edible species of Hygrophorus, locally named as Mitangjun or Qinggangjun, is widely distributed in southwestern China, and has long been named “Hygrophorus russula”. Morphologically, it is very similar to H. parvirussula and H. russula, but it can be distinguished from them by its usually dense pileus scales, distant, fragile, and pinkish white lamellae with pink to reddish discoloration of lamellar edge when mature, and white context when fresh and dried. Phylogenetically, this fungus forms an independent lineage according to the ITS analysis. Ecologically, it is typically associated with Quercus aquifolioides at high elevations (over 3000 m) in southwestern China. Therefore, it is treated as a new species, namely H. deliciosus.